(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This essay analyses the relationship between politics and science in the current health emergency phase. The role of the technical-scientific commissions set up by the Italian government to support political decisions is examined and it is compared with the models adopted by some foreign national systems. The Italian framework seems to be characterized by unpreparedness, whereas it would be necessary to establish steady rules of interaction between law and science.